The role of managed healthcare in the South African context: A systemic approach - P. F. Hugo; S. S. Loubser (South African Journal of Business Management, 2005)
Managed healthcare, in the context of this study, is defined as a series of management interventions in the healthcare supply chain, aimed at promoting appropriate and necessary care at a cost which is affordable to the consumer. It has evolved precisely because the healthcare supply chain is inefficient, too costly to be affordable to the majority of consumers in South Africa. Since managed healthcare represents a collection of interventions it is probable that these interventions will provoke responses which either support or counter the objectives of the intervening parties. The study focuses on trends which can be quantified in order to demonstrate this process, as well as on qualitative responses from role-players within the system, in order to explain behavioural changes that give rise to these trends.Managed healthcare is a management tool that is used in the private healthcare environment to manage the provision of care. In the past it was based on retrospective intervention and had cost containment as its main focus. Managed healthcare aims to address efficiency and quality of care but has yet to demonstrate measurable outcomes that would significantly impact on its WHO ratings. However, little attention is paid to the relationships and structure of the system within which care is provided and the dynamics that exist between and amongst role-players. The extent to which these relationships have an effect on the outcomes of the Private Healthcare Delivery System in South Africa is a relative unknown quantity. This article describes the research process which endeavours to develop a systemic approach to understand the current challenges in the PHDS better in order to optimise the outcome of it.
Keywords: 650